Tailoring the electrical and structural properties of sodium bismuth titanate with sintering temperature - Singh P.; Pandey R.; Singh P. (My University, 2025)
Na0.5Bi0.5TiO3(NBT) has attracted the attention of researchers because of the utilization of its accepter doped compositions as electrolyte materials in Solid Oxide Fuel Cells (SOFCs). This study reports the consequences of sintering temperature on the structural and electrical properties of sodium bismuth titanate (NBT). The NBT sample was synthesized using solid-state reaction route and sintered at two different temperatures. Both samples were characterized by X-ray diffraction, scanning electron microscopy and impedance spectroscopy techniques. X-ray diffractograms and its Rietveld refinement confirm the rhombohedral R3c symmetry with perovskite structures. SEM micrographs reveal grain growth with the rise in the sintering temperature. Impedance results in the frequency range of 24 Hz-1 MHz & temperature range of 500-700 °C suggest the increase in the conductivity with the sintering temperature. Moreover, the oxide ion migration pathway and energy barrier were analyzed using bond valance (BVE) analysis technique. © 2021 Elsevier Ltd. All rights reserved.